2023
DOI: 10.3390/foods12152896
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heat Treatment on the Digestion and Absorption Properties of Protein in Sea Cucumber Body Wall

Min Zhang,
Yuxin Liu,
Mengling Jin
et al.

Abstract: This study was designed, for the first time, to investigate the effect of oxidation on the digestion and absorption properties of protein in boiled sea cucumber body wall (BSCBW) via simulated digestion combined with everted-rat-gut-sac models. Boiling heat treatments led to protein oxidation in SCBW, manifested by increases in free radical intensity, thiobarbituric acid reactive substances, carbonyl groups, disulfide bonds, dityrosine bonds, advanced glycation end products, protein hydrophobicity and aggregat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…Обжарка позволяет существенно повысить усвояемость белка с 22,3% до 60,1% [12]. Это увеличение может быть связано с улучшением усвоения азота при нагревании, что делает белок более уязвимым для гидролиза [13]. Сделан вывод о необходимости учитывать обжарку для повышения эффективности использования проса.…”
Section: Introductionunclassified
“…Обжарка позволяет существенно повысить усвояемость белка с 22,3% до 60,1% [12]. Это увеличение может быть связано с улучшением усвоения азота при нагревании, что делает белок более уязвимым для гидролиза [13]. Сделан вывод о необходимости учитывать обжарку для повышения эффективности использования проса.…”
Section: Introductionunclassified
“…Roasting can significantly increase protein digestibility from 22.3 % to 60.1 % [21]. This increase may be due to improved nitrogen digestion when heated, making the protein more vulnerable to hydrolysis [22]. It is concluded that roasting should be taken into account to improve the efficiency of millet utilization.…”
Section: Introductionmentioning
confidence: 99%